Reducing Maternal Mortality : Learning from Bolivia, China, Egypt, Honduras, Indonesia, Jamaica, and Zimbabwe - Koblinsky, Marjorie A. (Washington, DC: World Bank, 2013)
Of the 515,000 maternal deaths that occur every year worldwide, 99 percent take place in developing countries. Women In the developing world have a 1 in 48 chance of dying from pregnancy-related causes; the ratio in industrial countries is 1 in 1,800. Of all the human development indicators, the greatest discrepancy between industrial, and developing countries is in maternal health. The stimulus for this study was the question - Can current program strategies reduce maternal mortality faster that the decades required in the historically successful countries of Malaysia, and Sri Lanka? The answer was no. Based on case studies in seven selected countries, the study stipulates the factor common to all reviewed programs, is the high availability of a provider who is, either a skilled birth attendant, or closely connected with a capable referral system. A second common factor is the high availability of facilities that can provide basic, and essential obstetric care. But, unlike historic successes however, strong government policy now focuses explicitly on safe motherhood, and sets the tone for programs in most of the selected countries. Another difference between the case studies selected, and that in historically successful countries, is the financing of services: while service were free to families in Malaysia and Sri Lanka, costs of safe motherhood services are now substantial, and a major deterrent to use.